Design and Assessment of Automatic Arc Welding Machine Based on Programming Logic Controller - Saini, Anuj; Rehalia, Vibhuti; Talgotra, Abhay; Shobit (International Journal of Engineering and Management Research, 2024)
In the industry, automated technologies have gained significant traction since they appreciably contribute to productivity and enable better, faster production with less worker management. Equipment used in welding processes in different locations might cause problems for the welder, particularly when large regions are needed. An Arc welding machine is commonly used in the Automobile industry, railroads, industrial piping, and bridge power plants. An arc welding machine requires skilled workers to be properly safe. The present research provides the design of an autonomous robotic arc welding system based on the benefits of employing programmable logic controller (PLC). In examine the benefits of PLC over traditional microcontroller solutions that are currently authorized for use in industrial settings, studies have been conducted on the behavior of a PLC responsible for carrying out the developed machine control functions. This study models automatic arc welding equipment that uses a PLC for safety purposes. The electrode is mounted on a welding tray that moves vertically up and down, joining sheets. The recently developed instrument is simple to use, accurate, precise, quick, cost-effective, and guarantees worker safety while in use.